1999
DOI: 10.1021/es980660s
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Speciation of Lead in Selected Mine Tailings from Leadville, CO

Abstract: We have characterized Pb speciation in selected tailings from the Leadville, CO, area using a variety of analytical techniques, including X-ray absorption fine structure (XAFS) spectroscopy. Samples from three locations were analyzed, including two chemically distinct tailings piles located within the city limits [Apache (pyrite-rich, low pH) and Hamms (carbonate-rich, near-neutral pH)] and tailings material deposited as overbank sediments along the Arkansas River approximately 13 km downstream from Leadville … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(163 citation statements)
references
References 38 publications
9
152
0
2
Order By: Relevance
“…The EXAFS-based speciation procedure for Hg is similar to that previously developed for and applied to other metal(loid)s such as arsenic (1,2) , lead (3)(4)(5) , and zinc (6,7) . It involves the comparison of an EXAFS spectrum collected from a Hg-bearing sample with a spectral library of model compounds previously generated from an assortment of Hg minerals and sorbed species (Figure 3).…”
Section: Mercury Speciation Protocolmentioning
confidence: 99%
“…The EXAFS-based speciation procedure for Hg is similar to that previously developed for and applied to other metal(loid)s such as arsenic (1,2) , lead (3)(4)(5) , and zinc (6,7) . It involves the comparison of an EXAFS spectrum collected from a Hg-bearing sample with a spectral library of model compounds previously generated from an assortment of Hg minerals and sorbed species (Figure 3).…”
Section: Mercury Speciation Protocolmentioning
confidence: 99%
“…For soils and sediments, the micrometer scale of resolution is appropriate because fine particles of similar composition and structure formed by biotic and abiotic natural processes tend to aggregate Isaure et al, 2002Isaure et al, , 2005Manceau et al, 2002b;Kirpichtchikova et al, 2003;Manceau et al, 2004;Sarret et al, 2004). This second approach is preferable because it is less invasive than chemical extraction (Ostergren et al, 1999;Calmano et al, 2001). Regardless of the approach used, the set of EXAFS spectra obtained either on soil fractions after physical or chemical treatments, or on minimally perturbed soil by µ-EXAFS, are analyzed by principal component analysis (PCA) (Wasserman, 1997;Wasserman et al, 1999;Ressler et al, 2000;Manceau et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…However, the existence of multiple species is a real limitation, and this drawback is generally overcome by fractionating the soil to reduce its heterogeneity in isolating or removing some metal species [2,3]. Still, this approach is not fully satisfying because it has been found that chemical and physical treatments can cause artefacts in modifying the very chemistry one is trying to probe [4]. In this work, we used the new combination of three synchrotronbased x-ray techniques, i.e., x-ray microfluorescence (µSXRF), microdiffraction (µXRD), and absorption spectroscopy (µEXAFS and bulk EXAFS), as discussed by Manceau, et.…”
Section: Introductionmentioning
confidence: 99%